â€œI ENJOY WRITING IN ENGLISHâ€: EFFECT OF USING POLITENESS IN WRITTEN DIRECT FEEDBACK - Ivo Dinasta Yanuar (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2022)
Giving feedback is not only doing correcting but also motivating the students to improve their competence especially in writing. Writing is perceived as the most diffcult skill because it requires good written communication skill. Similar to the students, the teacher is forced to have good written communication skill in commenting L2 learners’ writing. In commenting the error, politeness strategies are perceived as the best way to attract and motivate the students in giving written feedback. However, the study of giving feedback on students’ writing is still becoming hot issue. Therefore, this research studied about the effect of using politeness strategy in written direct feedback on students’ writing to fill the gap. There were experimental group (n = 5) and control group (n = 5) who must write their opinion in academic writing style. This study implemented quantitative and qualitative method with quasi-experimental study. Quantitative was used to find the effectiveness of the treatment by using ANOVA analysis while qualitative was applied to find the students’ opinion about the treatment. The result was satisfying because experimental group outperformed the control group.